2017
DOI: 10.1177/1073858417691030
|View full text |Cite
|
Sign up to set email alerts
|

The Glymphatic Pathway: Waste Removal from the CNS via Cerebrospinal Fluid Transport

Abstract: The overall premise of this review is that cerebrospinal fluid (CSF) is transported within a dedicated peri-vascular network facilitating metabolic waste clearance from the central nervous system while we sleep. The anatomical profile of the network is complex and has been defined as a peri-arterial CSF influx pathway and peri-venous clearance routes, which are functionally coupled by interstitial bulk flow supported by astrocytic aquaporin 4 water channels. The role of the newly discovered system in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 83 publications
1
113
0
5
Order By: Relevance
“…Thus, recurring sleep loss and/or impaired NREM sleep organization could determine long-term cognitive consequences, by impacting the pathways proposed to play a role in degenerative processes taking place in AD (Benveniste, Lee, & Volkow, 2017;Jessen, Munk, Lundgaard, & Nedergaard, 2015;Spira et al, 2016), through build-up and accumulation of hazardous wastes and may therefore extend the neurocognitive correlates of sleep to a longitudinal basis. On one hand, chronically increased synaptic load and strength and β-amyloid levels may be considered as a potential initiating and perpetuating factor in the pathological cascade.…”
Section: Recent Observations and Hypotheses Have Already Highlightedmentioning
confidence: 99%
“…Thus, recurring sleep loss and/or impaired NREM sleep organization could determine long-term cognitive consequences, by impacting the pathways proposed to play a role in degenerative processes taking place in AD (Benveniste, Lee, & Volkow, 2017;Jessen, Munk, Lundgaard, & Nedergaard, 2015;Spira et al, 2016), through build-up and accumulation of hazardous wastes and may therefore extend the neurocognitive correlates of sleep to a longitudinal basis. On one hand, chronically increased synaptic load and strength and β-amyloid levels may be considered as a potential initiating and perpetuating factor in the pathological cascade.…”
Section: Recent Observations and Hypotheses Have Already Highlightedmentioning
confidence: 99%
“…This allows them to get rid of damaged proteins by asymmetric division or apoptosis. Multicellular organisms, on the other hand, do the same, but the damaged proteins remain in the intercellular spaces or have to be expensively transported away (immune cells, [43,44]). We hypothetize that the outer cell layers (e.g.…”
Section: Organism Specific Issuesmentioning
confidence: 99%
“…Recent investigations revealed that CSF is exchanged rapidly with interstitial fluid by three highly organized pathways: 1. the para-arterial CSF route, 2. the paravenous interstitial clearance route and 3. The intracellular, transparenchymal-glial (astrocytic) route that connects the two mentioned paravascular routes [1,2,4,6]. We try to illustrate this system in Figure 2.…”
Section: Figure1 Scheme Of the Cerebrospinal Fluid Circulationmentioning
confidence: 99%
“…The glymphatic system is contemporarily one of the most studied functional systems of the human body [1][2][3][4][5][6]. Much work has also already been devoted to the significance of impaired function of the glymphatic system in the development of dementia and other neurodegenerative diseases [7,8,9].…”
Section: Introductionmentioning
confidence: 99%